Inclusive education services for the blind: Values, roles, and challenges of university EFL teachers - Alies Poetri Lintangsari; Ive Emaliana (Institute of Advanced Engineering and Science, 2020)
Implementing inclusive education, the process of providing all learners with equal educational opportunities, is a major challenge for many educational systems worldwide, for it requires changes to values, system, and practices. In the teaching of English as a foreign language (EFL) in university, teachers are expected to be able to select, transform, or augment Universal Design for Learning (UDL), and Differentiated Instruction (DI) as a framework to guarantee accessibility of all learner types to the learning environment by employing specific educational design guidelines, to fit their leaners', notably for the blinds. Data on what has led EFL teachers to join the reform of the teaching instruction and how they tackle problems during implementation cannot be located. Thus, the aim of this qualitative study is to uncover reasons for EFL teachers to participate in and what they did to facilitate the instruction wide effort to practice inclusive education, as well as challenges encountered. Key findings included implementing university policy as prime reasons for practicing inclusive education, utilizing UDL and DI as the key to successful implementation for instructional teaching, and inadequate resources and teacher training as the main challenges. Recommendations consists of providing disability-specific pre- and in- service training programs for teachers and making arrangements of sufficient educational materials and assessment based on UDL and DI towards EFL instructions.